The current and advanced situation of ram semen quality in Bangladesh - Mohammad Asaduzzaman; Farida Yeasmin Bari (Veterinary Integrative Sciences)
This study aimed to survey the literature on Bangladeshi rams’ semen characteristics, quality evaluation, and production required for sheep breeding and production strategy programs. The ram potentiality must be assessed to optimize production performance and maximize stakeholders’ use of high genetic values. This is usually accomplished through an andrological examination of the male, which evaluates the characteristics and quality of the sperm produced. Microscopic semen evaluations, such as sperm motility, viability, normal morphology, plasma membrane integrity, and acrosome integrity, and macroscopic semen evaluations, such as semen volume, color, and pH, enable the identification and removal of clear-cut cases of male infertility or subfertility. Therefore, the current paper reviewed, discussed, summarized, and compared all the research performed on Bangladeshi rams’ semen characteristics, quality evaluation, and production.